Neuropeptides in the Gonads: From Evolution to Pharmacology - Nicolette L McGuire; George E Bentley; George E Bentley (Frontiers Media S.A., 2010)
Vertebrate gonads are the sites of synthesis and binding of many peptides that were initially classified as neuropeptides. These gonadal neuropeptide systems are neither well understood in isolation, nor in their interactions with other neuropeptide systems. Further, our knowledge of the control of these gonadal neuropeptides by peripheral hormones that bind to the gonads, and which themselves are under regulation by true neuropeptide systems from the hypothalamus, is relatively meagre. This review discusses the existence of a variety of neuropeptides and their receptors which have been discovered in vertebrate gonads, and the possible way in which such systems could have evolved. We then focus on two key neuropeptides for regulation of the hypothalamo-pituitary-gonadal axis: gonadotropin-releasing hormone (GnRH) and gonadotropin-inhibitory hormone (GnIH). Comparative studies have provided us with a degree of understanding as to how a gonadal GnRH system might have evolved, and they have been responsible for the discovery of GnIH and its gonadal counterpart. We attempt to highlight what is known about these two key gonadal neuropeptides, how their actions differ from their hypothalamic counterparts, and how we might learn from comparative studies of them and other gonadal neuropeptides in terms of pharmacology, reproductive physiology and evolutionary biology.